Abstract 055: Reperfusion Therapy for Acute Ischemic Stroke in Cardiomyopathy Patients with Heart Failure: A NIS‐based Analysis - Serena Wong; Bridget Dolan; Fawaz Al‐Mutfi; Brittany Russo; Chaitanya Medicherla; Kevin Clare; Aiden Liu (Stroke: Vascular and Interventional Neurology)
Introduction Cardiomyopathy (CM) is a diverse pathology defined by both structural and functional changes in the heart. Many studies have aimed to determine if heart failure (HF) is an independent risk factor in the development of AIS, but there is a paucity of literature describing the interventions and functional outcomes in this group of patients. We aimed to investigate the safety of intravenous tissue plasminogen activator (IV tPA) and mechanical thrombectomy (MT) for acute ischemic stroke (AIS), and compare the functional outcome in cardiomyopathy patients with and without HF. We hypothesized that CM and HF patients would have higher rates of mortality and complications but would still benefit from reperfusion therapy with improved functional outcomes. Methods This is a multi‐center, retrospective study. The National Inpatient Sample (NIS) database from 2016‐2019 for patients with a principal diagnosis of AIS using the ICD‐10 code I63 was queried. AIS patients with CM and HF were compared to those without. Outcome measures studied included prolonged length of stay (LOS), discharge disposition, and inpatient mortality. Results We identified 2,939,160 patients with AIS between 2016 and 2019. Of those patients, 2.8% (80,915) had concomitant diagnoses of both CM and HF. Compared to matched cohorts, CM‐HF patients were more likely to be younger (age <80: 22.4% v. 27.3%, p < 0.001), male (61.8% v. 49.8%, p < 0.001), and African American (29.5% v. 16.4%, p < 0.001). Additionally, CM‐HF patients had higher rates of medical comorbidities such as atrial fibrillation (43.6% v. 24.2%, p < 0.001), diabetes mellitus (39.7% v. 37.6%, p < 0.001), obesity (9.2% v. 8.3%, p < 0.001), and obstructive sleep apnea (10.9% v. 7.3%, p < 0.001). CM‐HF patients were more likely to have an Elixhauser Comorbidity Index > 2 (99.4% v. 90.9%, p < 0.001). Lastly, this cohort was more likely to use anticoagulant medication (18.1% v. 9.5%, p < 0.001). CM‐HF patients were more likely to have a severe stroke (25.9% v. 19.6%, p < 0.001). Additionally, CM‐HF patients were more likely to receive both EVT (8.8% v. 5.6%, p < 0.001) and EVT and tPA (0.9% v. 0.6%, p < 0.001). An analysis of the rates of post‐intervention intracerebral hemorrhage showed that there was no significant difference observed between groups. This finding was regardless of the type of intervention received, including tPA (15.9% v. 13.6%, p = 0.192), EVT (15.6% v. 17.4%, p = 0.171), or both tPA and EVT (25.9% v. 22.3%, p= 0.321). CM‐HF patients had higher rates of in‐patient complications such as PEG placement, tracheostomy, sepsis, DVT or PE, pneumonia, UTI, AKI, myocardial infarction, and intracerebral hemorrhage. CM‐HF patients were more likely to have a prolonged LOS (47.8% v. 31.4%, p < 0.001) and higher rates of inpatient death (6.6% v. 5.4%, p < 0.001). Despite these outcomes, CM‐HF patients were less likely to have a non‐favorable discharge to both a skilled nursing facility (43.8% v. 44.9%, p < 0.001) and short‐term hospitalization (2.8% v. 4.6%, p < 0.001). Rates of favorable discharge were higher for CM‐HF patients (45.7% v. 43.9%, p < 0.001). Conclusion Patients with AIS and concomitant HF and CM are more likely to have favorable functional outcomes despite having higher rates of inpatient death and in‐hospital complications. Reperfusion therapies can be used safely in CM and HF patients.